2019
DOI: 10.2147/jmdh.s205608
|View full text |Cite
|
Sign up to set email alerts
|

<p>Abdominal Compartment Syndrome: Improving Outcomes With A Multidisciplinary Approach – A Narrative Review</p>

Abstract: Abdominal compartment syndrome (ACS) refers to a severe increase in intra-abdominal pressure associated with single or multiorgan failure. ACS with specific pathophysiological processes and detrimental outcomes may occur in a variety of clinical conditions. Patients with ACS are predominantly managed in critical care settings, however, a wide range of multidisciplinary interventions are frequently required from medical, surgical, radiological and nursing specialties. The medical management, aiming to prevent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 96 publications
0
30
0
10
Order By: Relevance
“…Recently, data on prevalence of IAH and ACS were summarized by Padar et al [5]. Data of 285 consecutive patients from a mixed medical-surgical intensive care unit (ICU) showed that ACS occurred in 3% of patients [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, data on prevalence of IAH and ACS were summarized by Padar et al [5]. Data of 285 consecutive patients from a mixed medical-surgical intensive care unit (ICU) showed that ACS occurred in 3% of patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-abdominal hypertension (IAH) is frequently present in critically ill patients and is an independent predictor for mortality [ 1 3 ]. When IAH progresses to abdominal compartment syndrome (ACS), organ failure occurs by definition [ 4 ] and mortality is very high [ 5 ]. World Society of the Abdominal Compartment Syndrome (WSACS, currently WSACS—the Abdominal Compartment Society) guidelines recommend protocolized monitoring of intra-abdominal pressure (IAP) in high-risk patients every 4–6 h [ 4 , 6 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Mortality is associated with the grade of IAH (Grade I: 10%-25%, Grade-II: 15%-45%, Grade III-IV: 50%-60%), and studies have found IAH to be an independent predictor of mortality[ 17 , 19 ]. ACS carries a mortality risk reported by 75%-90%[ 19 ].…”
Section: Epidemiology/mortalitymentioning
confidence: 99%
“…Continuous hemodynamic monitoring will guide goal-directed fluid resuscitation and the use of damaged control resuscitation as needed[ 2 ]. However, clinicians should keep in mind that parameters like central venous pressure, pulmonary capillary wedge pressure, ultrasound compression of inferior vena cava, mean arterial pressure, among others, may not be reliable during ACS[ 19 ].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation